PENGEMBANGAN KONSEP PENJUMLAHAN DAN PENGURANGAN MELALUI METODE JARIMATIKA PADA ANAK USIA DINI - Lathipah Hasanah; Marisah Tasha Sabrina; Siti Alfina Nazmi; Farida Azzahrah Anwar; Nurul Izzati (incrementapedia, 2022)
The purpose of this study was to determine the development of children's ability to recognize the concept of addition and subtraction using the Jarimatika method. Due to the inaccurate way of learning addition and subtraction, many children do not know the concept of addition and subtraction from 1 to 10. Fingering is a method of counting using fingers that can develop children's arithmetic abilities. In the math activities it is fun to introduce mathematics to children on the path of arithmetic, through from start to finish the game, let the children enjoy the fun of mathematics in math learning activities, no more problems in learning math activities. Methods to improve children's ability to learn to count and subtract and add operations using their hands. In this introduction to jarimatic, children can find out that mathematics is fun, especially in the way of counting. This research uses research methods of data collection techniques and literature studies or literature studies.